(untitled) (Research, Society and Development, 2026)
Introduction: Lithium carbonate plays an essential function in the management of mood disorders, standing out for its robust mood-stabilizing efficacy and its well-established protective effect against suicide. Nevertheless its application in emergency situations necessitates prudence owing to its low therapeutic index, very gradual initiation of action, coupled with the necessity for ongoing clinical and laboratory surveillance. Objective: To critically analyze the use of lithium carbonate in psychiatric emergencies, focusing on clinical indications, associated risks, management of intoxication, and implications for the organization of health services. Method: This is a narrative literature review based on a non-systematic search of the PubMed/MEDLINE, Scopus, and SciELO databases, complemented by international clinical guidelines, consensus statements from scientific societies, and classical psychiatric texts. Original studies, narrative and systematic reviews, clinical trials, observational studies, and normative documents relevant to the use of lithium in urgent and emergency contexts were included. Results: Lithium has well-established efficacy in acute mania, relapse prevention, and reduction of suicide risk. In emergency settings, its prescription should be limited to situations involving adequate clinical assessment, demonstrated capacity for adherence, absence of a recent history of intoxication or medication-related suicide attempts, and assurance of outpatient follow-up with appropriate laboratory monitoring. Lithium intoxication is potentially severe, requiring early recognition and prompt, appropriate clinical management. Conclusion: Despite its substantial benefits, the use of lithium carbonate in psychiatric emergencies must be judicious, individualized, and integrated into a comprehensive care plan that ensures continuity of treatment, with the goal of maximizing therapeutic benefits while minimizing preventable risks.